Verifying Relationship between Fovea Palatini, Vibrating Lines and Junction between Hard and Soft Palate - Thapa, Dipak; Chandra, Suresh; Karki, Sunita (Orthodontic Journal of Nepal, 2016)
Introduction: Locating and incorporating posterior palatal seal (PPS) in maxillary denture is an important clinical procedure for retention. The use of anterior and posterior vibrating lines, hard and soft palate junction, fovea palatini and hamular notches as references to locate PPS, are largely disputed. Objective: To verify the relationship between fovea palatini, anterior and posterior vibrating line, and hard and soft palate junction and their role in locating PPS area. Materials & Method: 50 subjects were randomly selected. In each subject, hard and soft palate junction, anterior and posterior vibrating lines and fovea palatini were located and marked. Using Vernier caliper and divider, the distance between these lines and fovea palatini were measured and assessed. Result: V44% showed fovea palatini at hard and soft palate junction, 24% between junction and anterior vibrating line/vibrating line, 6% at anterior vibrating line, 24% between anterior and posterior vibrating lines and 2% at posterior vibrating line. In 44%, hard and soft palate junction coincided with anterior vibrating line. In the rest, mean distance was 2.76 mm right, 2.38 mm mid line and 2.79 mm left. 20% subjects revealed one vibrating line; 80% subjects had two vibrating lines with the mean distance 5.55 mm on right, 6.22 mm mid line and 5.40 mm on left. Conclusion: Recording posterior palatal seal is an important clinical step thus arbitrarily scraping of the cast using fovea palatini and hamular notch as reference, should be discouraged. Locating anterior and posterior vibrating lines and using them to determine the posterior extension and PPS should be recommended. Orthodontic Journal of Nepal, Vol. 6 No. 1, June 2016, pp.32-34